Analisis Klasifikasi Tipe Iklim dari Data Curah Hujan menggunakan Metode Schmidt Ferguson di Kota Bandung - Catlya Noer Aime Salwanaina; Nike Meydita Nuur Hidayah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the classification of climate types in Bandung City, West Java based on rainfall data using the Schmidt-Ferguson method. Rainfall is an important factor that will be analyzed for the Schmidt-Ferguson method. The Schmidt-Ferguson method classifies climates into four types, namely dry, semi-dry, semi-humid, and humid. This method will compare the number of dry months and the number of wet months. One of the reasons for choosing this method is its ability to group climates based on monthly rainfall patterns accumulated over a period of 10 years. The rainfall data used was taken from the local meteorological station on the Central Statistics Agency website during the period 2013-2023. The results of the analysis show that Bandung City has climate characteristics that are influenced by geographical and topographic factors, with a climate classification dominated by the wet tropical climate type. This study is expected to provide useful information for environmental planning and water resource management in the area.